The digitalization technology for sustainable rural entrepreneurship: A structured review - Samsudin, Norsamsinar; Zakaria, Thuraiya; Osman, Juliana; Ramdan, Mohamad Rohieszan; Mohd Khalid, Intan Khasumarlina; Mohamad, Norhidayah; Hanafi, Hafizul Fahri; Sastraredja, Sutanto (Penerbit Akademia Baru, 2024)
Digitalization technology has emerged as a critical tool for promoting and sustaining rural entrepreneurship by providing greater access to information and new business opportunities. It can enhance the competitiveness of rural entrepreneurs by enabling them to leverage e-commerce platforms, social media, and other digital tools to access the global market. However, the uneven distribution of digital infrastructure and the lack of digital literacy in rural areas can create significant barriers to digital adoption and pose challenges to promoting sustainable rural entrepreneurship. Hence, this paper aims to structurally review related studies from 2 databases (Scopus and EconBiz) by utilizing Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). A total of 30 papers were eligible for evaluation. The findings were discussed based on three themes: the role, challenges and opportunities, and impact of digitalization technology on rural entrepreneurship. The adoption of digitalization technology among rural entrepreneurs has the potential to drive economic growth, create employment opportunities, and foster sustainable development in rural areas.